A Systematic Review of Videoconference-Delivered Psychological Treatment for Anxiety Disorders - Rees, Clare; Maclaine, E. (John Wiley and Sons Ltd, 2015)
Objective: Recently, increasing attention has been given to the issue of limited access to evidence-based psychological treatments. Factors affecting access can include geographical distance from service providers, lack of trained specialists, and prohibitive costs for treatment. Videoconferencing provides a convenient, low-cost alternative to in-person psychotherapy. Although videoconferencing treatment has been trialled for a vast array of mental health problems, surprisingly little research has been conducted exploring the efficacy of videoconferencing for the treatment of anxiety disorders. Anxiety disorders are highly prevalent and disabling conditions for which effective psychological treatment exists. The aim of the present study was to determine the state of the evidence with regard to the effectiveness of videoconference-delivered treatment for anxiety disorders. Method: Using preferred reporting items for systematic reviews and meta-analyses guidelines, we conducted a systematic review of all studies that primarily recruited individuals with anxiety disorders, published between 2004 and 2014. Results: We identified 20 studies involving a total of 613 participants. Of the included studies, 50% were uncontrolled and 50% were controlled trials. The majority of studies conducted to date focused on post-traumatic stress disorder (PTSD; n=10), followed by obsessive-compulsive disorder (n=5), mixed anxiety and depression (n=2), panic disorder (n=2), and social phobia (n=1). No studies were located that focused on investigating videoconference-delivered therapy exclusively for generalised anxiety disorder. Conclusions: Findings are discussed in terms of the accumulating evidence for the effectiveness of videoconference-delivered therapy to treat anxiety disorders and the need for more trials overall, but particularly for generalised anxiety disorder.